Cervical Hydatidiform Moles Pregnancy: Diagnosis and Treatment - Sastra Winata, I Gede; Kusuardiyanto, Popy; Aryana, Made Bagus Dwi; Mulyana, Ryan (Open Access Macedonian Journal of Medical Sciences, 2021)
Cervical partial hydatidiform mole is a rare condition and difficult to diagnose. A 39-year-old Balinese woman from Sanglah General Hospital, Bali, Indonesia complained vaginal bleeding with abdominal pain. The patient was diagnosed with a partial hydatidiform mole based on physical examination, ultrasound, beta HCG levels and pathology examinations. Mass evacuation surgery followed by arterial ligation to stop the bleeding and periodically examination of beta HCG levels was carried out until the 14th week after the procedure. Beta HCG decreased gradually to normal level and indicate no risk of trophoblastic malignancy. Establishing the early diagnosis significantly affects the outcome of patient. Keywords: partial cervical hydatidiform mole, blighted ovum, pregnancy, diagnosis, therapy.